From passive to active pitch regulation of wind turbines: Optimization method with numerical validation - Al-Abadi, Ali Kedher Kashin; Kim, You Jin; Park, Jinyoung; Kang, Hyunjin; Ertunc, Özgür; Delgado, Antonio (ASME Proceedings, Wind Energy Systems and Technologies, 2015)
An optimization method that changes the control strategy of the Horizontal Axis Wind Turbine (HAWT) from passive- to activepitch has been developed. The method aims to keep the rated power constant by adjusting the blade pitch angle while matching the rotor and the drive torques. The method is applied to an optimized wind turbine model. Further, numerical simulations were performed to validate the developed method and for further investigations of the flow behavior over the blades.
UnivIS-Import:2016-02-10:Pub.2015.tech.ITC.stmmec.frompa
Keywords: Cell engineering; Chemical analysis; Cooling systems; Electric power transmission networks; Numerical methods; Smart power grids; Solar power generation; Sustainable development; Wind power; Control strategies; Drive torque; Wind turbines